Uji validitas dan reliabilitas pediatric Sleep questionnaire terhadap Anak usia 6-18 tahun - Mufidah Nurul Hayati; Siti Chandra Dwidjayanti (Jurnal Kedokteran Gigi Terpadu, 2023)
Background: Sleep-breathing disorder (SBD) in children is strongly related to the number of dentofacial abnormalities. The manifestation of Children’s sleep problems can be misinterpreted as other pediatric conditions and affect the treatment accuracy. Instrument for screening need to be provided, therefore question about children’s sleep conditions need to be included. One of the instruments is Pediatric Sleep Questionnaire. In pediatric sleep studies, the application of sleep survey instruments has been applied but only a few reported the reliability or validity of the survey instruments. Purpose: The aim of the study is to produce accurate and reliable measuring devices to identify and assess sleep disorders that occur in children. Methods: This research was conducted using analytic observational with cross-sectional design at Tangerang City with 154 respondents who fulfilled inclusion and exclusion criteria. Spearman correlation test is used to measure the validity, Cronbach’s alpha is used to measure the reliability of each item question. Results: Based on the analysis, it showed snoring, sleepiness. and behavior showed a valid result, but two items showed invalid result. This can be caused by several factors; including limited parent’s knowledge and time to accompany children during sleep. Conclusion: This study shows that the PSQ has good validity and reliability which can identify and assess sleep problems in children aged 6-18 years.